Compulsive masturbation in a female: A case report and literature review - Ahmad Basri, Nadzirah; Wuing, Tan Sing (2018)
Background Compulsive masturbation has been defined as a non paraphilic sexual disorder. There is a scarcity of data on such populations. The disorder is rare and the majority of clients who seek treatment are males. Objective The purpose of this study was to present a case of compulsive masturbation in a Malaysian female to explore the meaning underlying the behavior and the tailored intervention administered. Method We report a case of a 23-year-old Malaysian female who presented herself to the Psychiatry Clinic to seek help regarding her compulsive masturbation problem which she has experienced for almost 10 years. It interfered with her daily and interpersonal functioning which leads to extreme guilt, shame and repeated repentance. She also displays depressive and anxiety symptoms. A psychosocio-spiritual therapy was administered with her to address feeling of low self-worth and revitalize her relationship with God. Results The client relates the meaning of her behavior with avoidance of disturbing feelings of loneliness and boredom and compensation for feelings of low self-esteem. Consequently, she resorted to sexual behaviors to compensate for the lack of inner resources and to supplement her self-esteem. Throughout therapy, her masturbation gradually decreased in number and duration until it no longer disturbed her daily functions. Conclusion The study results revealed that compulsive masturbation serve different psychological needs, which treatment expands beyond the overt sexual behavior. It is important that psychotherapy be administered after considering the sexual complaint, co-morbidity, cultural and religious background and motivation and life experiences of the client.